Entrepreneurship and Second-best Institutions: Going Beyond Baumols Typology - Robin Douhan; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2008)
This paper reconsiders the predominant typology pioneered by Baumol (1990) between productive, unproductive and destructive entrepreneurship. Baumols classificatory scheme is built around a limited concept of first-best outcomes and therefore easily fails to appreciate the true impact of entrepreneurship in real world circumstances characterized by suboptimal institutions. We present an alternative way of generalizing the notion of entrepreneurship and show how and why it encompasses the Baumol typology as a special case. Our main distinction is between business and institutional entrepreneurship. We draw on Schumpeters notion of creative destruction and reintroduce the entrepreneur as a potential disturber of an institutional equilibrium. Various subsets of institutional entrepreneurship are posited and discussed. It is shown that changing the workings of institutions constitutes an important set of entrepreneurial profit opportunities. An implication of this is that entrepreneurial efforts to reform or offset inefficient institutions can in some cases be welfare-improving.
Keywords: L50; M13; O17; O31; 330; Entrepreneurship; Innovation; Institutions; Entrepreneurship-Ansatz; Unternehmensgründung; Innovation; Schumpeterismus; Institutioneller Wandel